2020
DOI: 10.1186/s12957-020-01878-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes of gastric carcinoma with lymphoid stroma

Abstract: Background: Gastric carcinoma with lymphoid stroma (GCLS) is a rare subtype of gastric cancer. There have been several reports demonstrating the favorable prognosis of early GCLS without lymph node metastasis (LNM) compared with gastric adenocarcinomas. However, it remains unknown whether advanced GCLS (AGCLS) with LNM has a similar prognosis and clinicopathological features. This study aimed to assess the clinicopathological features of GCLS of all stages. Methods: We retrospectively assessed 375 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Previous studies have reported that patients with GMC significantly showed better overall and disease‐free survival 9,13 . In this study, overall survival was better in medullary carcinomas.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have reported that patients with GMC significantly showed better overall and disease‐free survival 9,13 . In this study, overall survival was better in medullary carcinomas.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have usually reported surgical treatment with endoscopic gastric mucosal dissection being feasible in the early stages and subtotal gastrectomy being required for advanced GCLS with lymph node metastasis. Postoperative chemotherapy may also be used but its efficacy remains unclear[ 11 ]. Programmed cell death (PD)-1/PD-L1 immunotherapy has been widely approved for treatment of lung cancer, liver cancer and other malignant tumors[ 12 ] but there are few reports on GCLS.…”
Section: Discussionmentioning
confidence: 99%
“…This type of tumor is frequently associated with Epstein-Barr virus (EBV) infection and sometimes shows microsatellite instability/mismatch repair deficiency [ 4 , 76 ]. Patients with this subtype show a lower number of lymph node metastases and better prognosis after surgery than those with other subtypes [ 77 , 78 ].…”
Section: Application Of Standard Pathology Reportmentioning
confidence: 99%